Strategy For Developing Fraud Prevention In The Implementation Of National Health Insurance At The Medan Baru Special Eye Hospital - Meliala, Sri Agustina; Sulisna, Aida; Humairoh, Rahma; Fitria, Dilla (Jurnal Kesmas Prima Indonesia, 2025)
Fraud In health, fraud is a form of fraud that includes misuse of assets and falsification ofstatements, which can be carried out by all parties involved in the service. BeBased on the initialsurvey conducted by the researcher, Medan Baru Eye Specialist Hospital has implemented apolicy to prevent fraud, one of the fraud incidents that has occurred is, patients using otherpeople's health insurance cards. The research method used in this study is a Mixed Method,namely a method that combines quantitative and qualitative approaches. The purpose of this studyis to analyze the implementation of prevention policies carried out by Medan Baru Eye SpecialistHospital in implementing health insurance programs. The results of qualitative research show thatthe hospital has built a fraud prevention system in accordance with PERMENKES No. 16 of 2019,and the results of quantitative research show that out of 100 respondents, 6% of patients stillcommit fraud. The conclusion in this study is that the preparation of fraud prevention policies andguidelines has been carried out with the formation of a Director's Decree, the development of afraud prevention culture, such as special socialization related to fraud has not been made., Thedevelopment of health services that are oriented towards quality control and cost control, stillneeds to be improved due to the many potential frauds that can be committed by patients andofficers, A fraud prevention team has been formed at Medan Baru Eye Specialist Hospital, MedanRumah, in accordance with the Director's Decree which regulates the duties of each member. Theimplementation of fraud prevention policies for patients has been successful, as evidenced byquantitative research showing that only 6% of patients still commit fraud. Hospitals are expectedto conduct specific outreach regarding fraud to all staff